Role of Cooperative Legislation in the Limitation of Informal Employment - ابراهيم, محمد عبد الرحمن (Journal of Legal Sciences, 2019)
In this study we examine the role that cooperative legislation can play in reducing informal employment. Cooperatives are considered the window of the social economy, which plays a major role in complementing traditional markets and collective labor, thus embracing the informal economy as the lifeboat for marginalized and excluded groups. Cooperatives come to regulate the informal economic sector as one of the options available for organization, by providing cooperatives in the provision of services and not by access to natural resources, and by facilitating the participation of decision makers in building skills for young people By supporting their ability to innovate, gaining the confidence of donor financial institutions, and ultimately influencing the political decision-making process, which is not without prejudice to a strategic framework through national legislation that is compatible with contemporary challenges, with financial support and ultimately democratic process through representation And social dialogue as the effective tools for the recognition of unorganized labor cooperatives.